Effectiveness of training stop‐smoking advisers to deliver cessation support to the UK national proposed standard versus usual care in Malaysia: a two‐arm cluster‐randomized controlled trial. (20th January 2021) - Wee, Lei Hum; West, Robert; Tee, Guat Hiong; Yeap, Lena; Chan, Caryn Mei Hsien; Ho, Bee Kiau; Perialathan, Komathi; Nik Mohamed, Mohamad Haniki; Michie, Susan; Jackson, Sarah E.
Abstract: Aims: To assess the effectiveness of training stop smoking services providers in Malaysia to deliver support for smoking cessation based on the UK National Centre for Smoking Cessation and Training (NCSCT) standard treatment programme compared with usual care. Design: Two‐arm cluster‐randomized controlled effectiveness trial across 19 sites with follow‐up at 4‐week, 3‐month, and 6‐month. Setting: Stop smoking services operating in public hospitals in Malaysia. Participants: Five hundred and two smokers [mean ± standard deviation (SD), age 45.6 (13.4) years; 97.4% male] attending stop smoking services in hospital settings in Malaysia: 330 in 10 hospitals in the intervention condition and 172 in nine hospitals in the control condition. Intervention and comparator: The intervention consisted of training stop‐smoking practitioners to deliver support and follow‐up according to the NCSCT Standard Treatment Programme. The comparator was usual care (brief support and follow‐up). Measurements: The primary outcome was continuous tobacco smoking abstinence up to 6 months in smokers who received smoking cessation treatment, verified by expired‐air carbon monoxide (CO) concentration. Secondary outcomes were continuous CO‐verified tobacco smoking abstinence up to 4 weeks and 3 months. Results: Follow‐up rates at 4 weeks, 3 months and 6 months were 80.0, 70.6 and 53.3%, respectively, in the intervention group and 48.8, 30.8 and 23.3%, respectively, in the control group. At 6‐month follow‐up, 93 participants in the intervention group and 19 participants in the control group were abstinent from smoking, representing 28.2 versus 11.0% in an intention‐to‐treat (ITT) analysis assuming that participants with missing data had resumed smoking, and 52.8 versus 47.5% in a follow‐up‐only (FUO) analysis. Unadjusted odds ratios (accounting for clustering) were 5.04, (95% confidence interval (CI) = 1.22–20.77, P = 0.025) and 1.70, (95% CI = 0.25–11.53, P = 0.589) in the ITT and FUO analyses, respectively. Abstinence rates at 4 week and 3 month follow‐ups were significantly higher in the intervention versus control group in the ITT but not the FUO analysis. Conclusions: On an intention‐to‐treat analysis with missing‐equals‐smoking imputation, training Malaysian stop smoking service providers in the UK National Centre for Smoking Cessation and Training standard treatment programme appeared to increase 6 month continuous abstinence rates in smokers seeking help with stopping compared with usual care. However, the effect may have been due to increasing follow‐up rates.